Community participation strategies to improve health in slum settings: a qualitative systematic review - Dambisya, Philip (Department of Public Health and Family Medicine, 2025)
With more than a billion people living in slum settings, the need to better health in slums is ever-growing. Community participation (CP) is continually gaining prominence as integral when addressing the complex challenges of those living in slums. Specific to health interventions in slums, an understanding of "what truly works" and what forms or approaches to CP support such efforts is under-researched. To understand the current knowledge base, this qualitative systematic review addressed the questions: What depth of community participation is seen in slum health improvement interventions, and what enables or constrains the deeper levels of participation? Articles were sought across ten databases: Academic Search Premier, Africa-Wide Information, APA PsycInfo, Business Source Premier, CINAHL, EconLit, Health Source: Nursing/Academic Edition, Scopus, SocINDEX with Full Text, and Web of Science. From the 653 unique studies identified, and subsequent citation tracking, reference list evaluation and snowballing further papers, nine articles published between 2000 and 2021 were included for review. Six of the studies were situated in the African region (three in South Africa, two in Kenya and one in Zimbabwe), two in South-East Asia (India) and one in South America (Brazil). Through a thematic analysis of the included papers, key themes of experiences were identified. The ‘depth' of participation of each reported slum health intervention was then assessed using Arnstein's ladder of citizen participation. In addition, the review identified what community participatory strategies were used within interventions in slum health contexts in low- and middle-income countries and analysed what factors enable or constrain CP. Six studies revealed that the interventions examined exhibited 'pseudo' forms of participation, with three presenting 'true' forms of participation. Findings revealed a mix of strategies within each intervention, but the number of CP strategies did not appear to affect the depth of participation in an intervention. Instead, the way in which a strategy was implemented appeared important – for example, establishing committees that represent the views of their constituents versus their own interests impacts on participation depth. In addition, integrating communities into planning and decision-making while engaging the broader social networks within communities in slums may lead to the improved buy-in of interventions. There is a need for an expansion of research in the field of slum health as well as ensuring that ways of assessing CP are included in evaluations of projects speaking to using CP as an underpinning concept of their actions.